Temperature influence on the triboelectric powder charging during dry coating of polypropylene with nanosilica particles - Düsenberg, Björn; Tischer, Florentin; Valayne, Erika; Schmidt, Jochen; Peukert, Wolfgang; Bück, Andreas (Powder Technology, 2022)
The influence of process temperature on the triboelectric charge during dry coating of cohesive polymer powders is investigated. The purpose of heating is to decrease the surface moisture of the powder, which results in an increase of electrical charge of the powder. The effect of the hydrophilicity of the SiO2 guest particles on the quality of the dry coating of PP host particles was investigated with respect to the integral charge of the dry coated powder. Furthermore, the flowability, crystallization behavior and degree of coverage (DOC) were investigated to determine the influence of the increased charge on these topics. Increased process temperature increases the electrical charge of the powder, which leads to a higher DOC with guest particles and, thus, drastically improved flowability compared to dry coating at ambient temperature. Furthermore, changes in the crystallization behavior of polypropylene are observed, due to more nuclei.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Crystallization; Dry coating; Flowability; Mixing; Polymer; Thermal treatment; Triboelectricity